Current use of phytogenic feed additives in animal nutrition: a review - Karásková, K.; Suchý, P.; Straková, E. (Czech Journal of Animal Science, 2015)
A rapid development in the potential use of phytogenic feed additives has occurred mainly due to the 2006 EU ban on the use of antimicrobial substances as growth stimulators; however, they are also used as sensory, technological additives or substances positively affecting the quality of animal products. The use of phytogenic additives in form of extracts, predominantly essential oils, has been tested in a number of animal species; however, there is still a lack of scientific findings on the safety and efficacy of their use, or on their effect on the quality of animal products. The aim of this review was to sum up current scientific knowledge on phytogenic additives in animal nutrition.
Keywords: phytogenics; essential oils; sensory; technological and zootechnical additives